Social advocacy cinema the mode of production by alternative multimedia collectives - Cabasal, Herwin Benedictos (2023)
Access online through this link: https://www.plarideljournal.org/article/social-advocacy-cinema-the-mode-of-production-by-alternative-multimedia-collectives
Keywords: Political films; Filmmaking; Social advocacy